Sustaining indigenous African choral music identity: A study on Ndwamaṱo George Mugovhani’s composition - Yende, Sakhiseni Joseph (Research Journal in Advanced Humanities, 2023)
Ndwamaṱo George Mugovhani is a distinguished scholar, emeritus professor, composer, and arranger of Venda choral music in South Africa. The researcher’s study uses the qualitative research method and the interview method grounded in autobiography theory to collect data about Mugovhani. As yet, Mugovhani’s contribution is undocumented. He is a well-recognised academic and NRF-rated professor. Mugovhani is an African music composer who played a significant role in establishing and preserving Venda choral music and African choral music identity in the twenty-first century. This study also provides an autobiography of Mugovhani that discusses his upbringing, schooling, and tertiary education, which shaped his career as a scholar and composer. Mugovhani’s notable compositions are Zwi Do Fhela Ngani, Zwi Do Fhela Ngani and Rendani Mapholisa, among many others. This article established that Mugovhani’s compositions use modality which is commonly used in African indigenous music. The article reveals that Mugovhani’s African compositions were largely influenced by Mzilikazi James Khumalo. The article affirms that Mugovhani’s compositions continue to sustain the South African Venda choral music identity. This article concludes by stating that the South African choral music genre has evolved as a unique genre that is rooted in indigenous African culture and identity.